Regions of our country and our world - Schreiber, Joan E.; Kain, Kathleen (Glenview, Ill. : Scott, Foresman, 1985)
A social studies textbook on the fourth grade level with an overview of the United States and selected regions of the world and with a special section on Indiana.
Keywords: Geography -- Juvenile literature; Geography; United States -- Geography -- Juvenile literature; Indiana -- Geography -- Juvenile literature; United States; Indiana